2006
DOI: 10.1111/j.1365-2729.2006.00173.x
|View full text |Cite
|
Sign up to set email alerts
|

How and what university students learn through online and face‐to‐face discussion: conceptions, intentions and approaches

Abstract: This paper reports a phenomenographic investigation into students' experiences of learning through discussion -both online and face to face (F2F). The study context was a second-year undergraduate course in psychology for social work in which the teacher had designed discussion tasks to begin in F2F mode and to continue online. A combination of open-ended questionnaires and semi-structured interviews was used to investigate students' conceptions of what they were learning, their intentions and their approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
0
15

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(116 citation statements)
references
References 27 publications
7
87
0
15
Order By: Relevance
“…In earlier research we have reported on the qualitative analysis of interview data in which students have told us about how they learn through discussions (Ellis et al, 2006). The context of that study was similar to the one described in this paper in both structure and content, as it was a pre-requisite for the course investigated in this Figure 1.…”
Section: Research Into Student Learning In Higher Educationmentioning
confidence: 99%
“…In earlier research we have reported on the qualitative analysis of interview data in which students have told us about how they learn through discussions (Ellis et al, 2006). The context of that study was similar to the one described in this paper in both structure and content, as it was a pre-requisite for the course investigated in this Figure 1.…”
Section: Research Into Student Learning In Higher Educationmentioning
confidence: 99%
“…Garrison and Vaughan (2008, p. 30) suggest that "the fusion of real and virtual experiences [through blended learning] creates unique communities of enquiry that are accessible regardless of time and location". While this was a critical aspect of module redesign, we were wary neither to overburden students nor to place competing time demands on them (Ellis et al, 2006). Ginns and Ellis (2007) have suggested that in adopting a blended learning approach, students must perceive the virtual learning component as a critical part of the module and understand its role in supporting the module as a whole.…”
Section: Teaching For Better Learning 329mentioning
confidence: 99%
“…Ellis et al (2006) argue that blended learning can be an important way of encouraging student discussion as the online and face-to-face environments provide diverse opportunities for discussion and peer engagement that may accommodate different kinds of learning styles and personalities. It is reasonable to suggest that the combination of environments and media used provides more opportunity to match teaching with a range of learning styles, potentially stimulates more interest and better engagement (El Mansour & Mupinga, 2007) and encourages greater democratization of the learning process.…”
Section: Teaching For Better Learning 329mentioning
confidence: 99%
“…Logan (2012) asserts that incorporating computer-based instruction enables students to learn more effectively than previously while also enhancing self-efficacy, learner satisfaction and instructional attitudes. Indeed, the use of online learning technologies has become a part of everyday experience of university students [12]. For example, the number of students who took at least one online subject was more than 1.6 million in 2002 and increased to 4.6 million in 2008 [13].…”
Section: Literature Reviewmentioning
confidence: 99%